Pengaruh Iklim Organisasi dan Motivasi Ekstrinsik Terhadap Komitmen Kontinuan Dengan Kepuasan Kerja Sebagai Variabel Mediasi pada Dinas Pertanian Kabupaten Deli Serdang - Lia, Mutiara Mey; Putra, Rizky; Suyar, Annisha Suvero (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to determine the effect of organizational climate and extrinsic motivation on continuance commitment, to determine whether job satisfaction mediates the effect of organizational climate on continuance commitment, to determine whether job satisfaction mediates the effect of extrinsic motivation on continuance commitment at the Agricultural Office of Deli Serdang Regency. The number of samples in this study was 114 respondents. The analysis technique used was path analysis. The results of the study indicate that organizational climate and extrinsic motivation have a positive and significant effect on continuance commitment, job satisfaction does not mediate the effect of organizational climate on work commitment and job satisfaction does not mediate the effect of extrinsic motivation on continuance commitment at the Agricultural Office of Deli Serdang Regency.